1988
DOI: 10.1002/pros.2990120403
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin and luteinizing hormone‐releasing hormone receptors in human benign prostatic hyperplasia and prostate cancer

Abstract: Using a sensitive micromethod for the determination of prolactin (PRL) binding sites based on 125I-human PRL ligand, PRL receptor levels in specimens of benign prostatic hyperplasia (BPH) and human prostate cancer were estimated by the one-point assay system. Ten of 19 BPH specimens (53%), showed significant PRL binding, four being in the 9-12 fmol/mg range. All ten of these cases had an histological diagnosis of nodular glandular hyperplasia. Of ten adenocarcinomas examined, four samples (40%) exhibited posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 42 publications
3
15
0
Order By: Relevance
“…The detection of membrane receptors for LH-RH in human and hamster pancreatic cancers and their absence in normal pancreas raises the intriguing possibility that LH-RH acting as a growth factor along with EGF might be involved in complex interactions that contribute to the appearance or promotion of pancreatic cancer. The demonstration of binding sites for [ D -T~~~I -L H -R H in pancreatic cancer is in agreement with similar findings on human breast, ovarian, and prostate cancers (17,(39)(40)(41)(42)(43). The exact mechanism by which LH-RH agonists inhibit the growth of these tumors is incompletely understood, but sex hormone deprivation would be among the principal effects in the case of prostate carcinoma, estrogen-dependent breast neoplasms, and possibly pancreatic cancer (3,17,(25)(26)(27)(28).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The detection of membrane receptors for LH-RH in human and hamster pancreatic cancers and their absence in normal pancreas raises the intriguing possibility that LH-RH acting as a growth factor along with EGF might be involved in complex interactions that contribute to the appearance or promotion of pancreatic cancer. The demonstration of binding sites for [ D -T~~~I -L H -R H in pancreatic cancer is in agreement with similar findings on human breast, ovarian, and prostate cancers (17,(39)(40)(41)(42)(43). The exact mechanism by which LH-RH agonists inhibit the growth of these tumors is incompletely understood, but sex hormone deprivation would be among the principal effects in the case of prostate carcinoma, estrogen-dependent breast neoplasms, and possibly pancreatic cancer (3,17,(25)(26)(27)(28).…”
Section: Discussionsupporting
confidence: 88%
“…The occurrence of SS-14 receptors in pancreatic cancers is also of potential interest, since it has been suggested that somatostatin analogs have direct antiproliferative effects on various tumors in addition to the inhibitory properties on the secretion of various hormones (18,24,26,(43)(44)(45)(46). Antitumor activity of somatostatin analogs on pancreatic cancers could be mediated through the inhibition of the secretion or action of gastrointestinal hormones such as gastrin and cholecystokinin (CCK), interference with the effects of growth factors, and directly through receptors for SS-14 located on the tumor cells (3,13,18,23-28,34,40,47).…”
Section: Discussionmentioning
confidence: 99%
“…The medical therapy for BPH and prostate carcinomas with GnRH analogues was presumed to work by decreasing testicular androgens through decreased LH levels and also by direct action of GnRH analogues on prostate tissue [42,43]. Because testicular androgens are already low, the therapeutic benefit of treatment with GnRH analogues may come from direct action as well as (in part) through decreased LH levels due to desensitization of anterior pituitary gland.…”
Section: Discussionmentioning
confidence: 99%
“…It is becoming clear that prolactin (PRL) is implicated in prostate growth (11)(12)(13)(14)(15) and in the development and regulation of BPH and prostate cancer (16)(17)(18)(19)(20). Some authors reported that PRL may promote the growth and proliferation of prostate cells in synergism with androgens (21), whereas others suggested that PRL has an independent action on prostatic growth and metabolism (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%